Petrographic and mineralogical characteristics of diagenetic overprinting in Neoproterozoic diamictites from Murchisonfjorden, Nordaustlandet, Svalbard - Bal Szczepan; Nejbert Krzysztof; Michalski Krzysztof; Domańska-Siuda Justyna; Manby Geoffrey; Hołda-Michalska Aleksandra; Sláma Jiři (Mineralogia)
The diagenetic processes exhibited by the Neoproterozoic diamictites from Murchisonfjorden (Nordaustlandet, NE Svalbard) are presented. Diamictite samples from the Cryogene Polarisbreen Group - the Petrovbreen Member of the Elbobreen Formation and the Wilsonbreen Formation were analysed. The mineralogical associations composed of chlorite group minerals (chamosite), albite, calcite, Fe-dolomite, clay minerals (illite) and quartz, recognized by integrated optical microscopy, scanning electron microscopy (SEM) and Raman spectroscopy techniques are typical for an advanced stage of mesogenetic diagenesis. Low-grade burial mineral associations were not identified. Our investigations indicate that during diagenesis increased heat flux accompanied fluid migration and remineralization. Identified Fe-Ti – oxides, anatase in thin sections and magnetite identified by rock-magnetic experiments are the products of the secondary diagenetic mineralization. The ferromagnetic carriers representing primary depositional remanence magnetization (DRM) were not preserved.